2015
DOI: 10.1111/rda.12639
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Slow‐Release Melatonin Improves Recovery of Ovarian Cyclicity and Conception in Summer Anoestrous Buffaloes (Bubalus bubalis)

Abstract: The role of melatonin as a protective neurohormone against restoring cyclicity in summer anoestrous animals in photoperiod species has gained wider acceptance. This study was designed to uncover the evidence the slow-release melatonin (MLT) has on initiation of ovarian cyclicity and conception rate (CR) in summer anoestrous buffaloes. Thus, buffaloes diagnosed as summer anoestrous (absence of overt signs of oestrus, concurrent rectal examination and radioimmunoassay for serum progesterone at 10 days interval) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(69 reference statements)
0
12
0
1
Order By: Relevance
“…It has been reported that melatonin implants in buffaloes can improve conception rate [12,15]. Melatonin treatment in buffalo is necessary to induce cyclicity during anestrus in out-of-breeding season in which evidenced an improvement in conception rate [42,43]. Ramadan et al [12,15] found that melatonin implantation alone did not affect the post-treatment reproductive performance in either anestrus buffalo or lactating buffaloes during out-of-breeding season.…”
Section: Methods To Manipulate the Out-of-season Breeding In Buffaloesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that melatonin implants in buffaloes can improve conception rate [12,15]. Melatonin treatment in buffalo is necessary to induce cyclicity during anestrus in out-of-breeding season in which evidenced an improvement in conception rate [42,43]. Ramadan et al [12,15] found that melatonin implantation alone did not affect the post-treatment reproductive performance in either anestrus buffalo or lactating buffaloes during out-of-breeding season.…”
Section: Methods To Manipulate the Out-of-season Breeding In Buffaloesmentioning
confidence: 99%
“…In anestrus lactating buffaloes injected with melatonin, the serum P4 concentrations increased (0.71 ng/ml) after melatonin injection compared with control group (0.28 ng/ml) at days 12 and 16 post-treatment (post-AI), during the summer season, suggesting a luteotrophic effect of melatonin [42]. Also, exogenous melatonin might improve uterine expression of P4 receptors or their binding capacity, which would result in higher reproductive efficiency [42].…”
Section: The Effect Of Exogenous Melatonin On Hormonal Levels and Blomentioning
confidence: 98%
See 2 more Smart Citations
“…Esses genes participam ativamente na formação da barreira hemato-testicular, regulação das células de Leydig, na espermatogênese e no mecanismo de apoptose(YANG et al, 2014). A administração exógena de melatonina diluída em veículo oleoso por via intramuscular é eficiente em aumentar a concentração sérica de melatonina por tempo prolongado em touros bovinos da raça Nelore.Para a escolha da concentração de melatonina a ser testada foi tomado por base a concentração descrita porKumar et al (2016) para bubalinos, os quais utilizaram a concentração de 18 mg/50 kg de peso vivo com resultados satisfatórios, conseguindo manter a concentração de melatonina elevada durante aproximadamente 20 dias, conforme ilustrado na figura 1. Porém, também foi testada uma concentração 50% maior, a fim de verificar se uma concentração maior seria mais efetiva.Figura 1: Concentração de melatonina sérica obtida por Kumar et al (2016) em animais tratados com 18 mg de melatonina para cada 50 kg de peso vivo em comparação com animais controle por 36 dias.…”
unclassified